Faktor-Faktor Yang Mempengaruhi Pendapatan Usaha Wirausaha Baru Pada Sektor Ekonomi Kreatif Di Kota Banjarmasin - Trie Prawitasari; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2021)
This study aims to (1) analyze the factors that influence the income of new entrepreneurs in the creative economy sector in Banjarmasin City (2) analyzing the dominant factors affecting the income of new entrepreneurs in the creative economy sector in Banjarmasin City. This type of research is a quantitative study using primary data obtained from questionnaires. Data was calculated by multiple linear regression analysis through the SPSS 26 program.The results of this study prove that the factors of working capital, education, age, working hours, and gender statistically jointly affect business income. This means anything of the size or level of working capital, education, age, working hours, and gender will greatly affect the income of new entrepreneurs in the creative economy sector in Banjarmasin City. In addition, this study proves that working capital is a dominant factor influencing the income of new entrepreneurs in the creative economy sector in Banjarmasin City. It can be seen that the results of the research have the most significant effect. This is caused by working capital is a factor that plays an important role in running a business.